ANALISIS PENERAPAN SISTEM MANAJEMEN KINERJA BERBASIS KOMPETENSI (STUDI PADA PT SINGLURUS PRATAMA) - Reza Revi Resyah; Fakhruddin Kurnia M; Sri Wirdana (Universitas Ichsan Sidenreng Rappang, 2024)
Human resources are a crucial element in achieving a company's objectives. The success of a company greatly depends on effective management of existing resources. Performance management plays a vital role in optimizing the performance of individuals, work units, and the company as a whole. A competency-based performance management system helps ensure that employee tasks and abilities align with the company's strategic goals. This system also contributes to rewarding high-performing employees who make significant contributions. PT Singlurus Pratama faces challenges in the coal industry and needs to enhance productivity through Competency-Based Human Resource Management (CBHRM). This research aims to explain the implementation of a competency-based performance management system at PT Singlurus Pratama and analyze its supporting and inhibiting factors. A descriptive research method with a qualitative approach is used to collect data through interviews, observations, and documentation. The research results indicate that employee awareness and discipline, collaboration between evaluators and employees, as well as technical and managerial support are the main supporting factors. However, subjectivity in evaluations, lack of employee involvement, and resistance to change are inhibiting factors that need to be addressed to achieve the success of the competency-based performance management system.